Teaching Technologies Online: Changes of Experience in Wartime in Ukraine - Sytnykova, Yu. V.; Shlenova, M.; Kyrpenko, Y.; Konoplenko, N.; Hrynchenko, I.; Kyrpenko, Y. (My University, 2023)
Online higher education in Ukraine has undergone changes during the Russian-Ukrainian war. Teaching online in wartime is stressful, but also encouraging; it is a way to overcome the stress of war. The purpose of the research is to showcase the changes in experience during wartime in Ukraine with respect to teaching methods and online technologies. To achieve the purpose, the methods of analysis and synthesis, questionnaires, and calculating methods, particularly MS Excel, are applied. There were 49 university teachers from Ukrainian government universities who took part in the study. The survey aims to fnd out how university teachers are ready to use new online teaching methods and techniques, to determine the priority in the method choice, and to indicate how to organize and have online lectures and practical classes. The following were the results observed: In the current situation, the relationship between teachers and students has become completely virtual. The teachers’ responsibility towards their students has increased signifcantly. Teachers are convinced of the global trend prospects of perceiving online teaching as one of the relevant and appropriate education forms in wartime Ukraine. It was online teaching that allowed students to continue their learning at Ukrainian universities, as many students were forced to leave their homeland, Ukraine, to save their lives. The conclusion is that teachers became more confdent in assessing their skills to organize online teaching, and they tried to develop them by mastering new Internet technologies for transferring educational content.
Keywords: online; method; technique; means; university; teacher; Ukraine